Violence in Quilombola women living in rural communities in Brazil - Luciano, Thaís Verly; Cislaghi, Beniamino; Miranda, Raquel Barbosa; Dias, Jerusa Araújo; Diaz-Bermudez, Ximena Pamela; Miranda, Angelica Espinosa (Revista de Saúde Pública, 2022)
OBJETIVE: To estimate the prevalence of psychological, physical, and sexual violence perpetrated against women by their intimate partner (IP) in Quilombola communities located in Espírito Santo State, Brazil. METHODS: The data is from a population-based cross-sectional study of Quilombola women conducted from 2017 to 2018. In-person interviews collected information on women’s sociodemographic characteristics, behaviors, and their experience of violence perpetrated by their IP. The analysis used chi-square test and hierarchical logistic regression. RESULTS: 219 women (94.8% of the invited ones) agreed to participate in the study. 59.0% (95%CI: 5.25–65.5) reported psychological violence; 41% (95%CI: 34.5–47.5) physical violence; and 8.2% (95%CI: 4.6–11.8) sexual violence. Psychological violence was associated with having three or more sexual partners in life, when compared to those who had up to two partners (p = 0,009), and previous violence involving other people outside of family increased the chance of suffering psychological violence by an IP more than nine times (p ≤ 0.001). Regarding physical violence, the association with use of barrier contraception (p = 0.031) and having a partner with other sexual partners (p = 0.024) were protective factors for IP violence. Having 3 or more sexual partners in the last 12 months (p = 0.006), partner using illicit drugs (p = 0,006), and alcoholism in the family (p = 0,001), increased the chance of suffer physical violence by the partner. Sexual violence perpetrated by the IP was associated with miscarriage (p = 0.016), partner using drugs (p = 0.020), and gynecological symptoms (p = 0.045). CONCLUSIONS: These results showed the high frequency of intimate partner violence in Quilombola women and highlight the importance of reducing social and race inequities for interrupting the culture of violence against women.